Teacher Trainers’ Training Practices in the Second Phase of Geography Teacher Training: Paths into Teacher Education, Training Practices, Potentials for Optimization - Fischer, Frank (Journal of Geography Education, 2023)
The second phase of teacher training is often considered to play a pivotal role in the professional development of prospective teachers. For Geography, there are hardly any findings on teacher trainers and their training practices. 23 Geography teacher trainers from twelve German states were interviewed in the context of a qualitative study. The paper provides findings about their paths into Geography teacher training, their initial and in-service training, as well as explorative insights into their training practices in seminar sessions and in reflective phases following the trainee teachers’ lessons. The paper closes by formulating ways to optimize the second phase of Geography teacher training.